2023
DOI: 10.1021/acsami.2c23169
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Substitution for BiVO4 to Enhance Photoelectrocatalytic Performance by Accelerating Polaron Hopping

Abstract: Bismuth vanadate (BiVO4) as a fascinating semiconductor for photoelectrocatalytic (PEC) water oxidation with suitable band gap (E g) has been limited by the issue of poor separation and transportation of charge carriers. Herein, we propose an unconventional substitution of V5+ sites by Ti4+ in BiVO4 (Ti:BiVO4) for the similar ionic radii and accelerated polaron hopping. Ti:BiVO4 increased the photocurrent density 1.90 times up to 2.51 mA cm–2 at 1.23 V vs RHE and increased the charge carrier density 1.81 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…56 Appropriate doping can tailor the optoelectrical properties of a semiconductor photocatalyst, thus greatly improving its PEC performance. Considering doping in BiVO 4 as an example, some metal impurity elements with relatively large atomic radii, such as Mo, Pt, Ti, Co, Ni, Zn and Cu, [57][58][59][60][61] can replace bismuth or vanadium elements, while some metals with relatively small atomic radii, such as Li, can enter the bismuth vanadate structure in the form of interstitial doping. 62 Some multiple metal ion cations and anions/cations can form co-doping in BiVO 4 , like V 5+ /Mo 6+63 and Mo 6+ /F À .…”
Section: Defects Of Different Dimensions and Atomic Structures In Pho...mentioning
confidence: 99%
“…56 Appropriate doping can tailor the optoelectrical properties of a semiconductor photocatalyst, thus greatly improving its PEC performance. Considering doping in BiVO 4 as an example, some metal impurity elements with relatively large atomic radii, such as Mo, Pt, Ti, Co, Ni, Zn and Cu, [57][58][59][60][61] can replace bismuth or vanadium elements, while some metals with relatively small atomic radii, such as Li, can enter the bismuth vanadate structure in the form of interstitial doping. 62 Some multiple metal ion cations and anions/cations can form co-doping in BiVO 4 , like V 5+ /Mo 6+63 and Mo 6+ /F À .…”
Section: Defects Of Different Dimensions and Atomic Structures In Pho...mentioning
confidence: 99%
“…[ 58 ] Alternatively, the direct spin coating of the FeOOH cocatalyst on Ti:BiVO 4 can also optimize the PEC performance. [ 29 ] Indeed, although these strategies can be used to improve the PEC water‐splitting performance, the cocatalyst layer may be uneven, which could lead to weak interfacial bonding and the generation of more defects. Owing to the simple superimposed operation of the cocatalyst loading, the interfacial adhesion between the photoanode and cocatalyst is often weak, which degrades the device performance because photogenerated carriers cannot be transported.…”
Section: Basic Principles For Pec and Cocatalystmentioning
confidence: 99%
“…Numerous studies have demonstrated that although the introduction of cocatalysts can efficiently improve the PEC performance, an additional interface is generated between the photoanode and oxygen evolution cocatalysts (Ph/OEC). [ 27 ] Limited by current cocatalyst‐loading methods (e.g., solvothermal, [ 28 ] spin coating, [ 29 ] and water baths [ 30 ] ), generated interfaces inevitably produce some defects during this process, which severely recombines photogenerated carriers. Furthermore, the contact force between the cocatalyst and photoanode is often weak, which hinders the transfer of photogenerated holes and degrades the long‐term operation of hybrid photoanodes.…”
Section: Introductionmentioning
confidence: 99%
“…16 However, the low electron mobility, surface recombination of charge carriers, and poor water oxidation kinetics of BiVO 4 limit its practical application in photoelectrochemistry. 25 Many modification strategies have been explored to promote charge injection at the electrode/electrolyte interface and accelerate the oxidation kinetics of surface water, including doping with different elements, 26 loading of oxygen evolution catalysts (e.g., FeOOH, 27 NiOOH, 28 and Co-Pi 29 ) and formation of heterojunction structures. 30 Therefore, the performance of PEC has improved effectively and the charge separation efficiency within the BiVO 4 bulk or at the interface has also increased.…”
Section: Introductionmentioning
confidence: 99%